Assessment for Septic Arthritis in Immunocompetent and Immunocompromised Patients: A Single-Institution Study. Issue 1 (1st January 2022) - Brown, Chelsea R.; Samade, Richard; Turnquist, Emily; Mickley, John; Lynch, Daniel; Larkin, Karilyn T. M.; Speeckaert, Amy L.
Abstract : Introduction: Prompt diagnosis of septic arthritis is imperative to prevent irreversible joint damage. Immunocompromised patients are at an increased risk of septic arthritis as well as secondary systemic infection. Our aims were to identify features predictive of septic arthritis and to determine whether these features differed between immunocompetent and immunocompromised patients. Methods: A single institution retrospective cohort study was performed of 173 immunocompetent and 70 immunocompromised patients who underwent aspiration or arthrotomy for suspected septic arthritis from 2010 to 2018. Demographic data, symptoms, laboratory values, and imaging findings were recorded. Multiple variable logistic regression models were used to assess for predictive factors for septic arthritis in both cohorts. Results were reported as odds ratios, 95% confidence intervals, and P values. Results: In the regression analysis, independent predictive factors for septic arthritis in immunocompetent patients were younger age ( P = 0.004), presence of radiographic abnormalities ( P = 0.006), and C-reactive protein (CRP) ( P < 0.001). For immunocompromised patients, only CRP was an independent continuous predictive factor ( P = 0.008) for septic arthritis. A risk stratification tool for predicting septic arthritis in immunocompetent patients using age <55 years, CRP >100 mg/dL, and presence of radiographic abnormalities was developed. A similar tool was created using CRP >180 mg/dL and radiographic abnormalities in immunocompromised patients. Discussion: Differences in predictive factors for septic arthritis between immunocompromised and immunocompetent patients suggest dissimilar clinical presentations. The developed risk stratification tools allow one to predict the likelihood of septic arthritis in both groups. This may permit more accurate selection of patients for surgical intervention in the setting of insufficient data from synovial aspiration.